Development of Islamic Education Management Framework for Increasing the Quality of Graduates - Novita, Mona (Institut Agama Islam Negeri Lhokseumawe, 2024)
The objectives of this study are: 1) To analyze the management of the basic components of Islamic education, 2) To analyze the development of a curriculum management framework for improving the quality of Indonesian graduates and 3) Analyze the role of the IQF as a Higher Education Curriculum in responding to problems in the quality of Indonesian graduates. The method used to answer this research is literature study. In order to answer the purpose of this study, library research methods were used. The data collection technique used is documentation technique with data analysis in the form of content analysis. In order to maintain the accuracy of the assessment and prevent misinformation in data analysis, bibliography checks and literature rereading are carried out. The results of this study are: 1) The basic components of Islamic education are: a) Islamic education personnel management. b) Islamic education student management, c) Islamic education curriculum management, d) Islamic education financial management and e) management of Islamic education facilities and infrastructure. 2) the development of a curriculum management framework to improve the quality of Indonesian graduates is carried out in three stages, namely: a) Curriculum Planning which is carried out starting from Strategic Planning, program planning, learning activity planning, b) curriculum implementation with four models: individual-based education program, learning , Module-based learning, competency-based education and school-based entrepreneurship c) Evaluation of the curriculum was carried out using the Saylor and CIPP Stufflebeam models. Saylor dan CIPP Stufflebeam.